Towards self-authorship: postgraduate psychology students' meaning-making journeys - Du Toit, Nadia (University of the Free State, 2017)
In this study, the meaning-making processes of postgraduate psychology students were explored as they move towards the development of self-authorship. During the period of emerging adulthood, individuals are afforded the freedom to explore and experiment with potential identity alternatives. Students enrolled at Higher Education Institutions (HEIs) represent a subgroup of emerging adults who experience unique challenges to their cognitive and psychosocial development. Baxter Magolda’s theory on self-authorship served as the theoretical framework for this study. Following a constructivist-developmental, narrative approach, Baxter Magolda plotted individuals’ journeys from an external to an internal way of making meaning within epistemological, intrapersonal, and interpersonal dimensions. Educational experiences challenge the cognitive and psychosocial development of students towards self-authorship. Postgraduate psychology students in particular, undergo a process of personal development and growth along with the acquisition of academic knowledge and skills. Sensitivity for their intrapersonal worlds and interpersonal dynamics as future mental health practitioners is essential. This qualitative research study followed a multiple case study approach rooted within a constructivist framework. Through purposive sampling, four postgraduate psychology students from the University of the Free State were selected to complete two reflective writing tasks and participate in two in-depth interviews during their honours year. The data were analysed thematically. Each participant’s experiences were reconstructed into main and subthemes. A cross-case analysis was also conducted, and the following themes were identified: In their search for self, participants’ experiences related to identity development, finding purpose and direction, and defining their own belief systems. Experiences that were identified as contributing to personal growth included the academic experience, specifically experiences intrinsic to the honours psychology programme and the selection process for the master’s degree. Participants were challenged to engage in personal reflection and critical thinking. Interpersonal relationships with classmates, friends, family, husbands, and lecturers were identified as either offering support and/or challenging current worldviews. Changes experienced included relational redefinition and restructuring, becoming more autonomous and independent, and questioning authority while listening to their internal voice to define their beliefs, identities, and ways of knowing. The findings of this study highlight the nuanced and cyclical pathway towards self-authorship of postgraduate psychology students who are expected to undergo significant intrapersonal growth and more advanced cognitive functioning as they journey towards becoming mental health professionals.

In hierdie studie is die betekenisvormende prosesse van nagraadse sielkunde-studente in hulle beweging na die ontwikkeling van selfouteurskap verken. Gedurende die tydperk van ontluikende volwassenheid word individue die vryheid gegun om potensiële alternatiewe identiteite te verken en daarmee te eksperimenteer. Studente wat by hoëronderwysinstellings ingeskryf is, verteenwoordig ŉ subgroep van ontluikende volwassenes wat unieke uitdagings tot hulle kognitiewe en psigososiale ontwikkeling ervaar. Baxter Magolda se teorie oor selfouteurskap het as die teoretiese raamwerk vir hierdie studie gedien. Deur ŉ konstruktivisties-ontwikkelende, narratiewe benadering te volg, het Baxter Magolda individue se reise van ŉ eksterne na ŉ interne manier van betekenisvorming binne epistemologiese, intrapersoonlike en interpersoonlike dimensies geskets. Opvoedkundige ervarings daag die kognitiewe en psigososiale ontwikkeling van studente in die rigting van selfouteurskap uit. Nagraadse sielkunde-studente in besonder ondergaan ŉ proses van persoonlike ontwikkeling en groei tesame met die verkryging van akademiese kennis en vaardighede. Sensitiwiteit vir hulle intrapersoonlike wêrelde en interpersoonlike dinamika as toekomstige geestesgesondheidspraktisyns is essensieel. Hierdie kwalitatiewe navorsingstudie het ŉ veelvuldige gevallestudie-ontwerp, gewortel in ŉ konstruktivistiese raamwerk, gevolg. Deur doelgerigte steekproeftrekking is vier nagraadse sielkunde-studente van die Universiteit van die Vrystaat gekies om twee reflektiewe skriftelike opdragte te voltooi en aan twee diepgaande onderhoude gedurende hulle honneursjaar deel te neem. Die data is tematies ontleed. Elke deelnemer se ervarings is in hoof- en subtemas geherkonstrueer. ŉ Kruisgeval-analise is ook uitgevoer, en die volgende temas is geïdentifiseer: In hulle soeke na die self het deelnemers se ervarings verband gehou met identiteitsontwikkeling, die vind van doel en rigting, en definiëring van hulle eie oortuigingstelsel. Ervarings wat geïdentifiseer is as bydraend tot persoonlike groei het die akademiese ervaring ingesluit, spesifiek ervarings inherent in die honneurs-sielkundeprogram en die keuringsproses vir die meestersgraad. Deelnemers is uitgedaag om deel te neem aan persoonlike nadenke en kritiese denke. Interpersoonlike verhoudings met klasmaats, vriende, familie, eggenote en dosente is geïdentifiseer as ondersteunend en/of uitdagend van huidige wêreldbeskouings. Veranderings wat ervaar is, het ingesluit relasionele herdefiniëring, groter outonoom- en onafhanklikheidwording en bevraagtekening van gesag terwyl hulle na hulle innerlike stem luister om hulle oortuigings, identiteit en manier van weet te definieer. Die bevindings van hierdie studie beklemtoon die genuanseerde en sikliese weg tot selfouteurskap van nagraadse sielkunde-studente van wie verwag word om beduidende intrapersoonlike groei en meer gevorderde funksionering te ondergaan op hulle reis om professionele geestesgesondheidswerkers te word.
Dissertation (M.A. (Psychology))--University of the Free State, 2016
Keywords: Self-authorship; Narrative identity; Emerging adulthood; Postgraduate psychology students; Education, Higher